Queries on queer cinema collective authorship within the independent queer film productions of Cinemalaya 2023 - Berame, Alec Tash S.
Anchored in three theories: Sellors’ (2007) collective authorship in film, Heath & Isbell’s (2021) principled collaboration, and De Ridder, Dhaenens, and Van Beuwel’s (2011) representational strategies of queer resistance, this study investigated collective authorship within the independent queer films productions of Cinemalaya 2023: Huling Palabas, Iti Mapukpukaw, and Rookie, as facilitated by collaboration and communication toward the manifestation of representational strategies of queer resistance. Through a qualitative case study design with 16 key informant interviews and three textual/film analyses, the study was able to surface that the filmmakers’ motivations, successes, and the challenges they experienced were observed to align with their intentions both at the individual and the collective level, paving the way for the collective authorship of their respective films. Within the process of collective authorship, the filmmakers were also found to collaborate toward goodness as facilitated by communication which were oriented through either dialogue, interests, conflict, consensus, and solutions. Such communications within the collaboration toward collective authorship were observed to inform the manifestation of queer resistance strategies within the scenes and sequences of the films. The findings highlight grounded perspectives about the role collective authorship plays in the production of independent queer films in the Philippines.